Strategy and Management of Dispute Resolution, Land Conflicts at the Land Office of Sleman Regency - Iswantoro Iswantoro (Lembaga Contrarius Indonesia, 2021)
Complex land disputes from time to time have increased both in quality and quantity. The cause is due to the needs of increasingly complex land use while minimal land availability. In addition, the cause can be triggered by any regulations that overlap and occur disharmony in its implementation. This problem is coupled with the lack of legal understanding in society due to acts committed on its soil and the publication of the registration system, which adopts negative publications, opening the faucet lawsuit and objections from other parties on the ground registered. Inequality in land ownership and the certificate and the use of land that is not following the location permit, allotment, use, and utilization of the land made into the complex problems of land disputes. This condition needs to be made to seek justice, legal protection, and law enforcement, namely the judiciary. In addition, the settlement of land disputes can flow through administrative channels that BPN, Mediation, Reconciliation, and ADR, which action significantly contributed to the completion of land disputes. Therefore, the necessary stakeholders to these ideals can be realized. Keywords: Dispute Resolution, Land Conflicts, Land Office